2012
DOI: 10.1371/journal.pone.0032147
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Targets for 17α-Ethynyl-5-Androstene-3β,7β,17β-Triol, an Anti-Inflammatory Agent Derived from the Human Metabolome

Abstract: HE3286, 17α-ethynyl-5-androstene-3β, 7β, 17β-triol, is a novel synthetic compound related to the endogenous sterol 5-androstene-3β, 7β, 17β-triol (β-AET), a metabolite of the abundant adrenal steroid dehydroepiandrosterone (DHEA). HE3286 has shown efficacy in clinical studies in impaired glucose tolerance and type 2 diabetes, and in vivo models of types 1 and 2 diabetes, autoimmunity, and inflammation. Proteomic analysis of solid-phase HE3286-bound bead affinity experiments, using extracts from RAW 264.7 mouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…The selectivity of HE3286 responses may be better understood based on recent investigations of HE3286‐binding partners, which were discovered using affinity chromatography and SILAC (stable‐isotope labeling in culture) proteomic analysis tools . We have evidence for direct interactions between HE3286 and both extracellular receptor kinase (ERK) 1 and 2, in addition to other binding partners.…”
Section: Discussionmentioning
confidence: 99%
“…The selectivity of HE3286 responses may be better understood based on recent investigations of HE3286‐binding partners, which were discovered using affinity chromatography and SILAC (stable‐isotope labeling in culture) proteomic analysis tools . We have evidence for direct interactions between HE3286 and both extracellular receptor kinase (ERK) 1 and 2, in addition to other binding partners.…”
Section: Discussionmentioning
confidence: 99%
“…We designed this study to test the hypothesis, based on preclinical data and on molecular studies of HE3286 binding partners, that HE3286 would decrease the hyperactivation of NFkB with consequent restoration of insulin signaling [5, 6], dependent on its interaction with extracellular signal regulated kinase (ERK) 1 and 2 [7] in addition to other binding partners. ERK1 is an important mediator of inflammation-induced insulin resistance [2325], insulin receptor substrate (IRS)-1 serine (inhibitory) phosphorylation, and the inhibitory effect of TNF α on insulin signaling [26].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, HE3286 reduced liver cholesterol and triglyceride content, leading to a feedback elevation of low-density lipoprotein (LDL) receptor and decreased total serum cholesterol [5]. Recently, we have reported that HE3286 binds to Erk1/2, Lrp1, and Sirt2 [7] and proposed that the HE3286-mediated decrease in hyperactivation of Erk1/2 may be causal for its metabolic [8] and anti-inflammatory activities. …”
Section: Introduction and Purposementioning
confidence: 99%
“…HE3286 ERK binding [19] and regulation of ERK activation [20] may be responsible for the anti-inflammatory and neuroprotective effects observed in the current study. MPTP initiates a neuroinflammatory sequence involving (among other inflammatory mediators) high mobility group box 1 (HMGB1) that prolongs ERK activation [11].…”
Section: Discussionmentioning
confidence: 99%
“…HE3286 has no known intrinsic neuropharmacological activity or toxicity [13]. HE3286 binds ERK1/2, low-density lipoprotein receptor-related protein 1 (Lrp1) and sirtuin 2 (Sirt2) [19], and HE3286 decreases ERK1/2 activation in lipopolysaccharide-(LPS)-stimulated rodent macrophages [20]. HE3286 is a Phase II clinical development compound with a good safety profile in humans to date (manuscript submitted).…”
Section: Introductionmentioning
confidence: 99%